Kewenangan Kepala Daerah dalam Menetapkan Karantina Wilayah untuk Mencegah Penularan Virus Covid-19: Perspektif Fiqh Siyasah Dusturiyyah - Resti Kurnia; Inagatha Setyarahma Pangastuti; Lailiah Novianti (Ma’mal: Jurnal Laboratorium Syariah dan Hukum, 2022)
Abstract: This article discusses the analysis of fiqih siyasah dusturiyah on the authority of regional heads in determining regional quarantine during the COVID-19 pandemic. This research is normative juridical research. The collected data were analysed in a descriptive method using the conceptual approach method l.  The results of this study concluded: first, the determination of regional quarantine by the Regional Head during the Covid-19 pandemic, when viewed from the positive law, is still not appropriate because it is not according to Law No. 6 of 2018 concerning health quarantine, in which it is explained that the one who has the right to determine regional quarantine is the Central Government.  This is a matter for the Central Government because it is related to national resilience, namely in the health sector. Second, the review of siyasah dusturiyah related to the determination of regional quarantine by the Regional Head is considered inappropriate because, in the Islamic government, there has been a division of duties that has been running since the time of the Prophet Muhammad SAW in Medina, as Head of State. There was tashri'iyah (legislative) power, tanfidziyah  (executive)  power, and qadla’iyah (judicial) power; the Prophet gave those duties to the companions who were capable and mastered his fields, although in general, it all came down to the Prophet as well. So it is the same if the authority of the Regional Head must also be based on instructions or approval from the Central Government. Keywords: Regional head, regional quarantine, Covid-19, fiqh siyasah. Abstrak: Artikel ini membahas tentang analisis fiqih siyasah dusturiyah terhadap kewenangan Kepala Daerah dalam penetapan karantina wilayah pada masa pandemi covid-19. Jenis penelitian yang ini adalah penelitian yuridis normatif. Data yang terkumpul dianalisis secara deskriptif dengan menggunakan metode pendekatan konseptual. Hasil penelitian ini menyimpulkan: pertama, penetapan karantina wilayah oleh Kepala Daerah pada masa pandemi covid-19 ini jika ditinjau dari hukum positif masih kurang tepat dikarenakan tidak sesuai dengan UU No. 6 Tahun 2018 tentang kekarantinaan kesehatan yang mana di dalamnya dijelaskan bahwa yang berhak menetapkan kekarantinaan wilayah ialah Pemerintah Pusat. Hal tersebut sejatinya menjadi urusan Pemerintah Pusat karena berkaitan dengan ketahanan nasional yakni di bidang kesehatan. Kedua, tinjauan siyasah dusturiyah terkait penetapan karantina wilayah oleh Kepala Daerah dianggap kurang tepat dikarenakan dalam pemerintahan Islam sudah ada pembagian tugas yang telah berjalan sejak zaman Nabi Muhammad SAW di Madinah, sebagai Kepala Negara. Ada kekuasaan tashri’iyah (legislatif), kekuasaan tanfidziyah (eksekutif), dan kekuasaan qadlaiyah (yudikatif). Nabi memberi tugas-tugas tersebut kepada para sahabat yang mampu dan menguasai bidang-bidangnya, meskipun secara umum semuanya bermuara kepada Nabi juga. Jadi sama halnya jika dengan kewenangan Kepala Daerah juga harus berdasarkan instruksi atau persetujuan dari Pemerintah Pusat. Kata kunci: Kepala daerah, karantina wilayah, Covid-19, fiqh siyasah.